THE POTENTIAL OF DIGITAL RUPIAH AS A NEW SOLUTION TO COMBAT CORRUPTION IN INDONESIAN GOVERNMENT - -, Dyah Tiara Putri Anggraeni; Enjat Munajat (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
Abuse of authority for personal gain through illegal behavior such as corruption and embezzlement of funds to a tax-free country is a big problem in government. The government's anti-corruption intelligence agency is often faced with difficulties in finding physical evidence of acts of corruption as a legal remedy in upholding justice. However, with the development of technology in the current digitalization era, money has become increasingly physical, and digital currency has developed rapidly throughout the world. In the near future, Indonesia will also soon have its own digital currency called Digital Rupiah. This will trigger changes in various transaction systems and the Indonesian economy. The purpose of this research is to reveal the potential of Digital Rupiah which can be a new solution to the eradication of corruption in the Indonesian government. This research uses a normative juridical approach with literature studies from various related literatures. With the right design and technology infrastructure in digital currency, the government will have accurate data on the amount and direction of money circulation that can be used to track corruption in the government. This article will also review the models, regulations, and risks mitigation needed to manage the potential of the digital rupiah in tackling the problem of corruption in government.